Soda Pulps from Nagaland Grasses for Writing and Printing Papers - Guha, S. R. D.; Singh, Man Mohan; Kumar, Krishan; Jadhav, A. G. (Indian Forester, 1974)
Systematic investigations were carried out on laboratory scale on three Nagaland grasses, viz., thatch (Imperata cylindrica), khagra (Neyraudia reynaudiana) and bhutang (Saccharum procerum) for finding the suitability of soda pulps prepared from them for production of writing and printing papers. It was found that except for khagra top portion, all three grasses were suitable. When pilot plants trial were carried out to confirm the laboratory trials, it was found that bhutang top portions also not suitable.